Patrimônio cultural, templo e ruína: a Igreja de São Miguel Arcanjo e os Potiguara de Baía da Traição, PB - Matheus Cassio Blach (2017)
This dissertation investigates the context involving the patrimonialization of the Church of São Miguel Arcanjo, located in Potiguara Brazilian natives land in Baía da Traição, Paraíba (PB). For this, a historical survey of this process was carried out, which has been confronted with theoretical perspectives from the field of historic preservation. It´s worth noting that since the listing of the church in 1980, no intervention was taken to safeguard it, which results in its ruin. Moreover, it is perceived that the safeguard instrument ends up distancing the local community from the cultural good which it should protect. Following this trajectory, our dissertation seeks to identify the discursive practices of social actors that fit into the conflicting relationship between heritage and power, as well as the narratives of memory and tradition. The main goal was to identify the symbolic value of this church for the Potiguara native people, as well as the values involved in its patrimonialization. In this sense, data related to the identity of the Potiguara people are analyzed, such as their history; their economy; their way of life; and the relation of the Potiguara with their territory, with the Catholic Church and with the manifestation of their religiosity in general